Foreign investors and risk shocks: seeking a safe haven or running for the exit? - Maurizio Michael Habib; Livio Stracca (European Central Bank (ECB), 2013)
In this paper we study the impact of shocks to global risk and global risk aversion (such as Lehman) as well as shocks with a more idiosyncratic nature (such as the euro debt crisis) on cross border portfolio flows, taking the perspective of foreign investors. We find robust evidence of systematic portfolio outflows in the wake of both types of shocks. There are no securities which are consistently safe haven assets, namely experiencing portfolio inflows when risk is on the rise or perceived to be high. Nevertheless, especially money market instruments issued by the US, euro area low-yield countries and Japan, as well as securities issued in Switzerland have behaved as safe haven assets in specific episodes or following changes in certain risk measures. We also find that the role of US-based crises and risk shocks is special, with the US not necessarily experiencing portfolio outflows or even attracting inflows for short-term dated securities, as a safe haven country, in those episodes.
Keywords: G11; G15; 330; home bias; Information; portfolio flows; risk aversion; safe haven